PELAKSANAAN PEMENUHAN HAK TERHADAP PERLINDUNGAN SAKSIDALAM TAHAP PENUNTUTAN TINDAK PIDANA KORUPSI OLEHJAKSA PENUNTUT UMUM DI PENGADILANTINDAK PIDANAKORUPSI PADA PENGADILAN NEGERI PEKANBARU - Ariska, Rafosa; Indra, Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Legal protection is a form of service that must be provided by the government to provide security to every citizen. The purpose of this thesis namely; First, to determine the implementation of the fulfillment of the right to the protection of witnesses in the stage of prosecution of corruption by the public prosecutor at the Corruption Court in the District Court Pekanbaru, second, to determine the barriers faced by the public prosecutor in the implementation of the fulfillment of the right to the protection of witnesses in stages prosecution at the Corruption Court in Pekanbaru District Court, Third, to know the efforts made by the prosecution in overcoming barriers to implementation of the fulfillment of the rights protection of witnesses in the prosecution phase at the Corruption Court in the District Court of Pekanbaru.In research there are three main things that can be inferred. First, the implementation of the fulfillment of the right to the protection of witnesses in the prosecution phase of criminal acts of corruption by the public prosecutor at the court of corruption in the District Court Pekanbaru not running optimally. Second, the barriers faced by the Prosecution in the implementation of the fulfillment of the rights of witnesses in the stage of prosecution of corruption in the corruption court in the District Court Pekanbaru is the lack of budget prosecutor, the weak performance of the Agency, and the lack of public knowledge, Third, efforts made by the Prosecutor general in overcoming obstacles to the implementation of the fulfillment of the right to the protection of witnesses is to increase the budget of the prosecutor, improving the performance of the Agency, and to increase public knowledge. Suggestions Writer, first, to the government to consider an increase in the budget cost of the prosecutor, Second, to establish the Agency representative in the region, Third, increase public knowledge about the rights of witnesses.Keywords: Protection - Witness – Corruption